2023
DOI: 10.1108/aeds-01-2023-0011
|View full text |Cite
|
Sign up to set email alerts
|

Education for sustainable development from the lenses of Malaysian school leaders: a preliminary study

Abstract: PurposeThe issue of Education for Sustainable Development (ESD) has been on the rise in recent years, with concerns being raised by various stakeholders about its potential effects on education and the environment. However, little research has been done into school leaders' fundamental challenges in addressing ESD.Design/methodology/approachA qualitative, single-case study was embarked on to examine the experiences of Malaysian school leaders who actively engaged ESD in their schools. The data were collected b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Another study (Shaafi et al ., 2021) showed average awareness of environmental issues among primary school principals in Kuala Lumpur. A study on school leaders' perspective on ESD indicated that the challenge of principals to enact ESD goals highly relies on their positive thinking, ESD knowledge, system thinking and curriculum adaptation., which is still underdeveloped (Zainal Abidin et al ., 2023a).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study (Shaafi et al ., 2021) showed average awareness of environmental issues among primary school principals in Kuala Lumpur. A study on school leaders' perspective on ESD indicated that the challenge of principals to enact ESD goals highly relies on their positive thinking, ESD knowledge, system thinking and curriculum adaptation., which is still underdeveloped (Zainal Abidin et al ., 2023a).…”
Section: Literature Reviewmentioning
confidence: 99%
“…When applied to ESD, systems thinking emphasizes the interconnectedness of social, economic and environmental factors and the need to address these interdependencies for sustainable development. Systems thinking theory highlights that the challenges of ESD cannot be viewed in isolation but should be considered within the broader context of the SDGs (Zainal Abidin et al ., 2023a). The SDGs provide a comprehensive framework for sustainable development, encompassing a wide range of interconnected issues such as poverty eradication, education, climate action and responsible consumption.…”
Section: Literature Reviewmentioning
confidence: 99%